MICROSATELLITE INSTABILITY AS A MOLECULAR GENETIC MARKER OF DEFECTIVE MISMATCH REPAIR SYSTEM IN ESOPHAGEAL CANCER - О. I. Kit; D. I. Vodolazhsky; E. N. Kolesnikov; N. N. Timoshkina; I. Yu. Efimova (Сибирский онкологический журнал, 2016)
Esophageal cancer is an aggressive form of cancer. Adenocarcinoma and squamous cell carcinoma are the most common histological types of esophageal cancer, with the incidence rate showing an upward tendency. Although endoscopic biopsy is considered the «gold standard» for diagnosis of esophageal cancer, both falsepositive and false-negative results can occur, therefore, the predictive and prognostic molecular markers in outcome of esophageal cancer are required. Although the molecular events involved in esophageal cancer pathogenesis are still poor understood, there have been reports on histological and genetic changes, such as DNA aberrant methylation and copy number variation, changes in DNA stability, its expression and etc. This review summarizes various investigations aimed at studying genomic instability (microsatellite instability, MSI), which predisposes the cell to malignant transformation. The mechanisms of interaction between the mismatch repair and miRNA expression in esophageal cancer have been studied. Recent advances in genomic and molecular studies of MSI+ cancers can successfully complement the histological assessment and help to develop novel therapeutic approaches to cancer treatment.